(untitled) (Research, Society and Development, 2021)
The main measures to fight the Covid-19 pandemic are based on social distancing and isolation. These measures aim to reduce the possibility of contamination, the demand for health services and the number of deaths. Despite the benefits it brings, social isolation often implies experiencing unpleasant situations that can impact the mental health of those involved. Therefore, this study aimed to analyze the impact of Covid-19 on the quality of life of the elderly, as the older population is part of the group with the highest risk of developing the severe form of the disease. The present study is exploratory-descriptive, with a quantitative character and characterized in the context of metric studies of information, especially scientometrics. Thus, we sought to understand the dimension of scientific studies in the field of Covid-19 and its impact on the quality of life of the elderly, emphasizing the current state of the art. To meet the proposed objective, the bibliometric method Proknow-C was used to select relevant articles on the impact of Covid-19 on the quality of life of the elderly. After an extensive literature search, the current study confirmed mental health and physical activities being impaired in the present pandemic scenario, implying the importance of managing these problems and continuously caring for health care for the elderly. Based on these findings, we can conclude that there is a strong association between the impact of Covid-19 on mental health and physical activities in the elderly.